Photograph of a room in the Beethoven-Haus with bust of A. W. Thayer (2023)
Sepia photograph of a room in the Beethoven-Haus with the bust of A. W. Thayer by Francesco Pezzicar placed in the corner. Written in pencil on verso (in Susan Thayer Fox's hand): "This is a corner in the Beethoven house with my uncle's bust"; (in an unidentified hand): "corner of Beethoven Haus mit bust of A. W. Thayer."